Inducible protein knockout reveals temporal requirement of CaMKII reactivation for memory consolidation in the brain - Wang, Huimin (The National Academy of Sciences, 2003)
By integrating convergent protein engineering and rational inhibitor design, we have developed an in vivo conditional protein knockout and/or manipulation technology. This method is based on the creation of a specific interaction interface between a modified protein domain and sensitized inhibitors. By introducing this system into genetically modified mice, we can readily manipulate the activity of a targeted protein, such as α-Ca(2+)/calmodulin-dependent protein kinase II (αCAMKII), on the time scale of minutes in specific brain subregions of freely behaving mice. With this inducible and region-specific protein knockout technique, we analyzed the temporal stages of memory consolidation process and revealed the first postlearning week as the critical time window during which a precise level of CaMKII reactivation is essential for the consolidation of long-term memories in the brain.